An aqueous lithium / sodium hybrid ion battery with directional ion transport channels
By using NATI2 (PO4) 3∥limn2O4 electrode materials and LN-SDS-N electrolytes in the water system lithium/sodium ion battery to form a directional ion transmission channel, solve the problem of cycle stability and perception performance of water-based ion battery, realized Excellent electrochemical performance at room temperature and low temperature.
Patent Information
- Application Number
- CN202210280489.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-03-21
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2042-03-21
AI Technical Summary
The existing water-based ion batteries have high reactivity in the electrolyte, resulting in poor circulation stability. While improving the ionic conductivity of the electrolyte, it usually damages the rate performance of the battery.
A NaTi2(PO4)3∥LiMn2O4 aqueous ion battery is used, and LN-SDS-n is used as the electrolyte. LN-SDS-n is composed of lithium sulfate, sodium sulfate and sodium dodecyl sulfate, through SDS micelle clusters The orderly arrangement forms a directional ion transmission channel, inhibiting the reactivity of water molecules and improving ion conductivity.
It significantly improves the cycle stability and magnification performance of the lithium/sodium ion battery, and maintains excellent electrochemical properties under low temperature conditions.
Smart Images

Figure CN114937821B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrochemical energy storage and relates to an aqueous lithium / sodium mixed ion battery with a directional ion transmission channel. Background Art
[0002] Ion batteries using organic electrolytes are referred to as organic ion batteries, and ion batteries using aqueous electrolytes are referred to as aqueous ion batteries. Compared with organic ion batteries, aqueous ion batteries have the advantages of being environmentally friendly, having high rate performance, and having no safety hazards, and therefore have received widespread attention (Chem. Soc. Rev. 2020, 49, 180-232).
[0003] According to the literature (Nature Chemistry 2010, 2, 760-765), suitable negative electrode materials for aqueous ion batteries with an output voltage less than 2V are Li4Ti5O 12 , Mo6O8, TiO2, TiS2, VO2, LiTi2(PO4)3, NaTi2(PO4)3 and zinc flakes. Suitable cathode materials include LiCoO2, LiMn2O4, LiNiO2, LiNi x Mn 2-x O4, LiMnPO4, LiNi x Mn y Co z O2 (x+y+z=1), manganese oxide and Prussian blue analogs, etc. Relative to Li / Li + Lithium-containing metal oxides or phosphates have high redox potentials and are therefore commonly used as positive electrode materials for aqueous ion batteries.
[0004] Given the scarcity of lithium resources, lithium-ion batteries are not only expensive, but also difficult to meet the needs of the rapid development of electric and hybrid vehicles. In the periodic table, Na is adjacent to Li. In the "rocking chair" battery, Na + With Li + The ions have similar insertion and extraction mechanisms, and sodium resources are abundant; therefore, aqueous sodium batteries have developed rapidly.
[0005] As mentioned above, the cathode materials suitable for aqueous sodium batteries are very limited. In recent years, researchers have developed a hybrid ion battery (ChemSusChem 2014, 7, 2295-2302), which is a hybrid ion battery with Li + and Na + The electrode materials for intercalation and deintercalation are positive and negative electrodes. Hybrid ion batteries not only enrich the types of ion batteries, but also simplify the selection of positive and negative electrode materials for ion batteries.
[0006] Due to the dissolution of electrode materials when in contact with water and the electrochemical side reactions between water and electrode materials, ion batteries assembled with aqueous electrolytes generally have the problem of poor cycle stability. Reducing the reactivity of water in the electrolyte can inhibit electrode side reactions and improve the cycle stability of aqueous ion batteries (Science 2015, 350, 938-943; Nat. Energy 2016, 1, 16129). However, while reducing the reactivity of water in the electrolyte, the ionic conductivity of the electrolyte is usually impaired (Nat. Mater. 2020, 19, 1006-1011), thereby impairing the rate performance of the battery.
[0007] Therefore, solving the contradiction between the increase in ionic conductivity of aqueous electrolytes and the decrease in water reaction activity not only has important scientific significance, but also is expected to obtain aqueous ion batteries with improved rate performance and cycle stability. Summary of the invention
[0008] In view of the shortcomings of the prior art, the present invention provides an aqueous lithium / sodium ion battery with a directional ion transport channel, which can simultaneously improve the cycle stability and rate performance of the aqueous lithium / sodium ion battery.
[0009] The present invention provides a NaTi2(PO4)3||LiMn2O4 (hereinafter referred to as NTP||LMO) aqueous ion battery, wherein NaTi2(PO4)3||LiMn2O4 refers to a battery in which the negative electrode material is NaTi2(PO4)3 (hereinafter referred to as NTP) and the positive electrode material is LiMn2O4 (hereinafter referred to as LMO). The NTP||LMO aqueous ion battery has an NTP working electrode as the negative electrode, an LMO working electrode as the positive electrode, LN-SDS-n as the electrolyte, and a diaphragm between the positive and negative electrodes.
[0010] Preferably, the NTP∥LMO aqueous ion battery has a discharge capacity of 28-47.1 mA hg after 2000 cycles at room temperature. -1 , capacity retention rate is 61.9-70%,
[0011] Preferably, the NTP / LMO aqueous ion battery is at room temperature 0.2C (1C = 133mAg -1 ) is 55.6-67.1 mA h g -1 The discharge capacity at 5C is 8-44 mAh g -1 .
[0012] The present invention also provides an assembly method of a NTP / LMO aqueous ion battery based on LN-SDS-n, the steps of which are as follows:
[0013] 1) Preparation of working electrode
[0014] Take appropriate amount of electrode material powder, acetylene black and polyvinylidene fluoride, transfer them to an agate mortar, add appropriate amount of N-methylpyrrolidone, grind them thoroughly, and prepare slurry;
[0015] The slurry is evenly coated on the current collector, and then placed in a vacuum drying oven and dried at 75-85° C. for 10-14 hours to obtain a working electrode.
[0016] 2) Preparation of electrolyte
[0017] Use distilled water as solvent to prepare 0.5-1 mol L -1 Li2SO4 and 0.5-1mol L -1 Mixed solution of Na2SO4 V mL, solution A is obtained;
[0018] Add SDS to solution A, seal, stir at room temperature for 10 minutes, and then let stand until it becomes a transparent, bubble-free mixed solution to obtain LN-SDS-n. The amount of SDS used is 288.38×8.4×n×V / 1000, where 288.38 is the molecular weight of SDS, 8.4 is the cmc of SDS at room temperature, and n=30-120. Sealing is to prevent the electrolyte from absorbing moisture and falling into dust.
[0019] 3) Assembly of aqueous ion batteries
[0020] The R2032 button cell was assembled with NTP working electrode as negative electrode, LMO working electrode as positive electrode, LN-SDS-n as electrolyte and a separator between the positive and negative electrodes.
[0021] The electrode material powder described in step 1) includes NTP powder and LMO powder; the NTP working electrode is prepared by using the NTP electrode material powder, and the LMO working electrode is prepared by using the LMO electrode material powder.
[0022] Preferably, in step 1), the mass ratio of the electrode material powder, acetylene black and polyvinylidene fluoride is 8:1:1.
[0023] Preferably, in step 1), the current collector is a stainless steel mesh or a carbon cloth.
[0024] Preferably, in step 1), the mass of NTP on the negative electrode is 2-3 mg cm -2 , the ratio of the mass of LMO on the positive electrode to the mass of NTP on the negative electrode is 13:12.
[0025] Preferably, in step 3), the diaphragm is Whatman TM GF / A glass fiber paper or BH5510 sulfonated diaphragm.
[0026] Preferably, in step 1), the slurry is evenly coated on the current collector, and then placed in a vacuum drying oven and dried at 80° C. for 12 hours.
[0027] Preferably, in step 2), LN-SDS-n, wherein n=75-105; preferably, n=30, 60, 90, 120. Further preferably, the LN-SDS-n, wherein n=90.
[0028] Preferably, in step 2), the concentrations of lithium sulfate and sodium sulfate are both 0.5-1 mol L -1 .
[0029] Preferably, in step 2), the ionic conductivity of the LN-SDS-n at -15°C to room temperature (25°C) is 13-93 mS cm -1 .
[0030] Preferably, in step 2), the freezing point of the LN-SDS-n is -(3-4)°C.
[0031] Preferably, in step 2), the electrochemical stability window (ESW) of the LN-SDS-n is 1.78-2.06 V. The electrochemical stability window is the electrochemical window in which the electrolyte is tested without hydrogen and oxygen evolution.
[0032] Beneficial Effects
[0033] 1. Compared with the traditional NTP∥LMO with Li2SO4-Na2SO4 mixed solution as the electrolyte, the NTP∥LMO aqueous ion battery based on LN-SDS-n provided by the present invention has a discharge capacity of 28-47 mAh g after 600 cycles at room temperature 1C, 200 cycles at 2C, 400 cycles at 5C, and 800 cycles at 1C. -1 The capacity retention rate is 61.9-70%, and the capacity retention rate and cycle stability are significantly improved.
[0034] 2. The NTP∥LMO aqueous ion battery based on LN-SDS-90 exhibits excellent electrochemical performance at low temperatures (0°C and -15°C); after 5000 consecutive cycles at zero degrees, the NTP∥LMO discharge capacity is 35.2mAg -1 , the capacity retention rate is 93.1%; after 1000 cycles at -15℃, the NTP∥LMO discharge capacity is 10.7mAg -1 , the capacity retention rate is 71.3%. However, NTP∥LMO with Li2SO4-Na2SO4 mixed solution as electrolyte cannot work at -15℃. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is the LSV curve diagram of LN-SDS-n.
[0036] Figure 2 This is the ESW curve of LN-SDS-n.
[0037] Figure 3 This is the Raman spectrum of LN-SDS-n.
[0038] Figure 4 This is the conductivity curve of LN-SDS-n.
[0039] Figure 5 This is the differential scanning calorimetry curve of LN-SDS-n.
[0040] Figure 6 This is the freezable water content diagram of LN-SDS-n.
[0041] Figure 7 This is the molecular dynamics simulation diagram of LN-SDS-90 at room temperature.
[0042] Figure 8 This is the molecular dynamics simulation diagram of LN-SDS-0 at room temperature.
[0043] Fig. 9 For low temperature applied voltage (2V nm -1 ) under the action of LN-SDS-90 molecular dynamics simulation diagram.
[0044] Fig.10 This is the charge and discharge curve of NTP∥LMO at room temperature and 0.2C.
[0045] Fig.11 This is the rate performance diagram of NTP∥LMO at room temperature.
[0046] Fig.12 This is the cyclic stability diagram of NTP∥LMO at room temperature.
[0047] Fig.13 This is the cycling stability diagram of NTP∥LMO at 0℃, and the electrolyte is LN-SDS-90.
[0048] Fig.14 This is the cycling stability diagram of NTP∥LMO at -15°C, and the electrolyte is LN-SDS-90. DETAILED DESCRIPTION
[0049] The technical solution of the present invention is further described below through specific embodiments in combination with the accompanying drawings. These embodiments are only for illustrating the technical solution of the present invention and cannot be regarded as limiting the content of the claims of the present invention.
[0050] Lithium sulfate, sodium sulfate, sodium dodecyl sulfate, and N-methylpyrrolidone in the examples were purchased from Shanghai Sinopharm Chemical Reagent Co., Ltd. TM GF / A glass fiber paper, acetylene black and polyvinylidene fluoride were purchased from Taobao Jinghong New Energy Online Store, stainless steel wire mesh was purchased from Shanghai Xing'an Screen Manufacturing Factory, carbon cloth was purchased from Taiwan Carbon Energy Technology Co., Ltd., BH5510 sulfonated diaphragm was purchased from Shenzhen Gebang Technology Co., Ltd., NTP powder was homemade according to the reference (J.Alloys Compd.2019,782,576-585), and LMO powder was purchased from Jining Wujie Technology Co., Ltd.
[0051] Raman spectrum was obtained by Renishaw inVia plus Raman spectrometer; differential thermal analysis was obtained by TAInstruments DSC2500 scanning differential calorimeter; rheological properties were obtained by TADHR-2 interfacial rheometer; electrochemical properties of LN-SDS-n and NTP∥LMO batteries were obtained by Shanghai Chenhua CHI760E electrochemical analyzer and Wuhan Lanhe CT2001A; theoretical simulation was calculated using GROMACS software package.
[0052] Example 1
[0053] The preparation steps of LN-SDS-0 are as follows:
[0054] Using distilled water as solvent, prepare 0.5 mol L -1 Li2SO4-0.5mol L -1 20 mL of Na2SO4 mixed solution was added to obtain LN-SDS-0.
[0055] The preparation steps of LN-SDS-n are as follows:
[0056] 1) Using distilled water as solvent, prepare 0.5 mol L -1 Li2SO4-0.5mol L -1 20 mL of Na2SO4 mixed solution to obtain solution A;
[0057] 2) Add a certain amount of SDS to solution A, seal, stir at room temperature for 10 minutes, and then let stand until it becomes a transparent, bubble-free mixed solution to obtain LN-SDS-n. Specific data are shown in Table 1.
[0058] Table 1 Preparation data of LN-SDS-n
[0059]
[0060] Results Analysis
[0061] Figure 1 The room temperature linear sweep voltammetry (LSV) diagram of LN-SDS-n. Figure 1 It can be seen that the electrochemical stability window (ESW) of LN-SDS-n (n ≥ 1) is located at 1.78-2.06 V relative to the reversible hydrogen electrode (Table 1), which is greater than 1.72 V of LN-SDS-0. Moreover, as n gradually increases, the ESW gradually increases to 2.06 V for LN-SDS-90 and then decreases to 2.02 V for LN-SDS-120 ( Figure 2 ). This is attributed to the formation of hydrogen bonds between the SDS head group and water molecules, which can reduce the reactivity of water molecules. LSV results show that the directional dynamics of water molecules in LN-SDS-n and the hydrogen bonds between the SDS head group and water molecules do not have a linear dependence on the SDS concentration.
[0062] Raman spectroscopy can reflect the reactivity of water molecules in the system. Figure 3 is the Raman spectrum of LN-SDS-n. Figure 3 It can be seen that when n ≥ 30, the spectrum appears at 2800-3000cm -1 The stretching vibration peaks attributed to CH3 and CH2 groups indicate the presence of SDS. Importantly, as n increases from 1 to 90, the peaks at 3000-3800 cm -1 The OH stretching vibration peak of LN-SDS-90 has been clearly described), and its intensity gradually decreases; when n increases from 90 to 120, the OH stretching vibration peak intensity increases instead. Raman spectroscopy results show that the reactivity of water in LN-SDS-90 is the lowest; this is consistent with the results of LSV.
[0063] The ionic conductivity of LN-SDS-n at room temperature to -15°C was measured and calculated using electrochemical impedance spectroscopy. Figure 4 ).Depend on Figure 4 It can be seen that the conductivity of LN-SDS-n (n = 60, 90, 120) is significantly higher than that of LN-SDS-0 and LN-SDS-30, and is also significantly higher than that of the classic 21m LiTFSI "salt-in-water" electrolyte ( Figure 4 21 m LiTFSI was used for comparison). In addition, the room temperature conductivity of LN-SDS-n (n = 30, 60, 90, 120) (50-93 mS cm -1 ), which is comparable to 10-40m HCOOK, 10-30m KOAc and 25mLiNO3, and higher than other low-cost “salt-in-water” and molecular crowding effect organic fluoride electrolytes (see Table 2).
[0064] Importantly, the low temperature conductivity of LN-SDS-n (n = 30, 60, 90, 120) is excellent. For example, at -15°C, the conductivity of LN-SDS-n (n = 30, 60, 90, 120) is 13-17 mS cm -1 , while the conductivity of 25m LiNO3 at 10℃ is only 0.016mS cm -1 (Angew. Chem. Int. Ed. 2021, 60, 19965-19973), there is no data reported for 25m LiNO3 at sub-zero temperatures. As the temperature decreases, the conductivity decreases, which is a general rule. Therefore, below zero degrees Celsius, the conductivity of LN-SDS-n (n = 30, 60, 90, 120) is much higher than that of 25m LiNO3.
[0065] Table 2 Comparison of room temperature ionic conductivity of different electrolytes
[0066]
[0067] Among LN-SDS-n (n=30, 60, 90, 120), LN-SDS-90 has the highest conductivity at different temperatures. This is because as n increases, the charge carrier concentration in the electrolyte increases, but the viscosity of the electrolyte also increases at the same time. Compared with LN-SDS-90, the lower conductivity of LN-SDS-120 is attributed to the increase in system viscosity, resulting in the binding effect of SDS micelles on cations exceeding the contribution of the increase in charge carrier concentration to conductivity.
[0068] The content of freezable water in aqueous electrolyte is an important indicator for evaluating its low-temperature (≤0℃) operation reliability. Figure 5 The LN-SDS-n differential scanning calorimetry curve is given. Figure 5 It can be seen that as n increases by 30, the freezing point of the electrolyte decreases from -2.52°C of LN-SDS-0 to -4.03°C; and then as n increases, the freezing point of the electrolyte gradually increases to -3.07°C of LN-SDS-120. This shows that the addition of SDS is beneficial to lowering the freezing point of the electrolyte, but the decrease in the freezing point is not linearly related to the increase in SDS concentration. In addition, sodium sulfate and lithium sulfate in the system make important contributions to lowering the freezing point of the electrolyte. For example, the freezing point of SDS-90 (the electrolyte does not contain lithium sulfate and sodium sulfate, and the concentration of SDS is 90cmc) is -0.35°C, which is significantly higher than -3.71°C of LN-SDS-90. Therefore, the decrease in the freezing point of LN-SDS-n is attributed to the reaction between SDS and Li + / Na + and SO4 2- The synergistic effect of Figure 5 The data can be used to calculate the content of freezable water in the electrolyte. Figure 6 As shown, the variation trend of the freezable water content in LN-SDS-n is consistent with its freezing point; that is, the lower the freezable water content, the lower the freezing point of the electrolyte.
[0069] Although the freezing point of LN-SDS-n is not lower than -4.03℃, LN-SDS-n (n=30,60,90,120) still has high ionic conductivity at -15℃. To explain this experimental result, we performed molecular dynamics simulation using LN-SDS-90 as an example. The simulation results show that the SDS micelle clusters in LN-SDS-90 at room temperature are orderly arranged to form a directional ion transport channel ( Figure 7 ), while in LN-SDS-0, ions are randomly distributed in the electrolyte in the form of clusters at room temperature and cannot form qualitative ion transport channels ( Figure 8 ). At low temperature (-15-0℃), SDS and Li in LN-SDS-90 + / Na + and SO4 2- Ions are randomly distributed, and no directional ion transport channel is formed; under the action of electric field (0.5-2V nm -1 ), the SDS micelle clusters in LN-SDS-90 are orderly arranged to form a qualitative ion transport channel, and the charge carriers form a quasi-continuous ion flow in the channel ( Fig. 9 ), which ensures the high ionic conductivity of LN-SDS-90 at low temperatures.
[0070] Therefore, the electrolyte composition of aqueous lithium / sodium ion batteries with directional ion transport channels is a mixture of lithium sulfate (Li2SO4)-sodium sulfate (Na2SO4)-sodium dodecyl sulfate (SDS), abbreviated as LN-SDS-n. L represents lithium sulfate, N represents sodium sulfate, and SDS is sodium dodecyl sulfate; n represents the concentration of SDS in the electrolyte as a multiple of its critical micelle concentration (cmc). The critical micelle concentration (cmc) of SDS is 8.4mmol L at room temperature. -1 , the data comes from Biomacromol.2019,20,4361-4369. In the electrolyte, the reactivity of water is suppressed, and a directional ion transport channel can be formed at room temperature without an external electric field or at -15-0°C with an external electric field. The charge carriers can form a quasi-continuous ion flow in the channel, ensuring the high ionic conductivity of the electrolyte over a wide temperature range, which is beneficial to improving the room temperature and low temperature electrochemical performance of aqueous lithium / sodium ion batteries. The directional ion transport channel is a channel formed by the orderly arrangement of SDS micelle clusters, and the conductive ions are transported in one-dimensional direction in the channel, while the non-conductive ions or their clusters are randomly distributed.
[0071] Example 2
[0072] Assembly of NTP∥LMO aqueous ion battery:
[0073] 1) Take appropriate amount of electrode material powder, acetylene black and polyvinylidene fluoride (mass ratio 8:1:1), transfer them to an agate mortar, add appropriate amount of N-methylpyrrolidone, grind them thoroughly, and prepare a slurry;
[0074] 2) The slurry was evenly coated on a stainless steel mesh (current collector), and then placed in a vacuum drying oven and dried at 80° C. for 12 h to obtain a working electrode.
[0075] 3) With NTP working electrode as negative electrode, LMO working electrode as positive electrode, LN-SDS-0 as electrolyte, Whatman TM GF / A glass fiber paper separator, assembled R2032 button cell.
[0076] Example 3
[0077] Assembly of NTP|LMO aqueous ion battery. The difference between Example 8 and Example 7 is that the electrolyte is LN-SDS-1.
[0078] Example 4
[0079] Assembly of NTP|LMO aqueous ion battery. The difference between Example 9 and Example 7 is that the electrolyte is LN-SDS-30 and the diaphragm is a BH5510 sulfonated diaphragm.
[0080] Example 5
[0081] Assembly of NTP|LMO aqueous ion battery. The difference between Example 10 and Example 7 is that the electrolyte is LN-SDS-60 and the current collector is carbon cloth.
[0082] Example 6
[0083] Assembly of NTP|LMO aqueous ion battery. The difference between Example 11 and Example 7 is that the electrolyte is LN-SDS-90 and the diaphragm is a BH5510 type sulfonated diaphragm.
[0084] Example 7
[0085] Assembly of NTP|LMO aqueous ion battery. The difference between Example 12 and Example 7 is that the electrolyte is LN-SDS-120 and the current collector is carbon cloth.
[0086] Results Analysis
[0087] Fig.10 LN-SDS-n is used as the electrolyte, NTP∥LMO is at room temperature 0.2C (1C = 133mAg-1 ) under the charge and discharge curve. Fig.10 It can be seen that when n is equal to 0, 1, 30, 60, 90, and 120, the discharge specific capacities of NTP∥LMO are 59.4, 67.1, 62.8, 60.9, 65.1, and 55.6 mAh g, respectively. -1 . Importantly, with LN-SDS-n (n ≥ 1) as the electrolyte, the coulombic efficiency of NTP∥LMO charging and discharging is significantly improved, which means that LN-SDS-n (n ≥ 1) can improve the reversibility of the electrode reaction. In addition, compared with LN-SDS-n (n = 0, 1, 30, 120), with LN-SDS-60 and LN-SDS-90 as the electrolyte, the discharge specific capacity of NTP∥LMO at different current densities is significantly improved, and it still has a high discharge specific capacity at 5C ( Fig.11 and Table 3). This shows that LN-SDS-60 and LN-SDS-90 can improve the rate performance of NTP∥LMO.
[0088] Table 3 Comparison of room temperature discharge specific capacity of NTP∥LMO under different electrolytes
[0089]
[0090] Fig.12 is the room temperature cycling stability diagram of NTP∥LMO. Fig.12 It can be seen that with LN-SDS-0 as the electrolyte, NTP∥LMO was cycled 600 times at 1C, and the discharge specific capacity was 17.1mAg -1 , the capacity retention rate is only 26.9%. However, with LN-SDS-n (n=60, 90, 120) as the electrolyte, the NTP∥LMO discharge specific capacities are 40.5, 47.1 and 28.4 mA g-1 after 600 cycles of charge and discharge at 1C, 200 cycles at 2C, 400 cycles at 5C, and 800 cycles at 1C, for a continuous charge and discharge cycle of 2000 cycles. -1 , and the corresponding capacity retention rates are 61.9%, 70.4% and 66.2%, respectively. It can be seen that LN-SDS-n (n = 60, 90, 120) can significantly improve the electrochemical cycling stability of NTP∥LMO.
[0091] Fig.13 The cyclic stability diagram of NTP∥LMO at zero degrees with LN-SDS-90 as the electrolyte. Fig.13 It can be seen that after 600 cycles at 1C, 1000 cycles at 2C, 2000 cycles at 5C, 1000 cycles at 2C, and 400 cycles at 1C, the NTP∥LMO discharge capacity is 35.2mAg -1, the capacity retention rate is 93.1%. Even at -15℃, 200 cycles at 1C, 200 cycles at 2C, 600 cycles at 1C, and 1000 cycles continuously, the NTP∥LMO discharge capacity is 10.7mAg -1 , the capacity retention rate is 71.3% ( Fig.14 ), showing excellent low temperature cycling stability.
[0092] In summary, the present invention provides an aqueous lithium / sodium mixed ion battery with a directional ion transport channel. The reaction activity of water molecules in the electrolyte of this ion battery is suppressed, and it has a high ionic conductivity in the range of room temperature to minus 15°C. Compared with traditional aqueous lithium / sodium mixed ion batteries, the aqueous lithium / sodium mixed ion battery provided by the present invention has excellent rate performance and electrochemical cycle stability, and has a high discharge specific capacity and excellent cycle stability at minus 15°C. The aqueous lithium / sodium mixed ion battery provided by the present invention has broad application prospects in the field where the output voltage is less than 2V.
Claims
1. A NaTi2(PO4)3||LiMn2O4(NTP||LMO) aqueous hybrid ion battery with directional ion transport channels, characterized in that: The NTP working electrode is used as the negative electrode, the LMO working electrode is used as the positive electrode, LN-SDS-n is used as the electrolyte, and a separator is added between the positive and negative electrodes; The mass of NTP on the negative electrode is 2-3 mg cm -2 , the ratio of the mass of LMO on the positive electrode to the mass of NTP on the negative electrode is 13:12; The electrolyte was prepared as follows: Use distilled water as solvent to prepare 0.5-1 mol L -1 Li2SO4 and 0.5-1mol L -1 Mixed solution of Na2SO4 V mL, solution A is obtained; Sodium dodecyl sulfate (SDS) was added to solution A, sealed, stirred at room temperature for 10 minutes, and then allowed to stand until it became a transparent, bubble-free system to obtain a Li2SO4-Na2SO4-SDS mixed solution, referred to as LN-SDS-n; the amount of SDS used was 288.38×8.4×n×V / 1000, n=90; The NTP∥LMO aqueous ion battery has a discharge capacity of 28-47.1 mA hg after 2000 cycles at room temperature. -1 The capacity retention rate is 61.9-70%; the NTP∥LMO aqueous ion battery has a discharge capacity of 55.6-67.1 mA hg at room temperature and 0.2C. -1 ; The discharge capacity at 5C is 18-51mA hg -1 ; The LN-SDS-n has an ionic conductivity of 13-93 mS cm at -15°C to room temperature (25°C). -1 ; The LN-SDS-n has a freezing point of -(3-4)°C; The LN-SDS-n has an electrochemical stability window (ESW) of 1.78-2.06V.
2. The method for assembling the NTP / / LMO aqueous ion battery according to claim 1, comprising the following steps: 1) Preparation of working electrode Take appropriate amount of electrode material powder, acetylene black and polyvinylidene fluoride, transfer them to an agate mortar, add appropriate amount of N-methylpyrrolidone, grind them thoroughly, and prepare slurry; The slurry is evenly coated on the current collector, and then placed in a vacuum drying oven and dried at 75-85°C for 10-14h to obtain a working electrode; 2) Preparation of electrolyte Use distilled water as solvent to prepare 0.5-1 mol L -1 Li2SO4 and 0.5-1mol L -1 Mixed solution of Na2SO4 V mL, solution A is obtained; Sodium dodecyl sulfate (SDS) was added to solution A, sealed, stirred at room temperature for 10 minutes, and then allowed to stand until it became a transparent, bubble-free system to obtain a Li2SO4-Na2SO4-SDS mixed solution, referred to as LN-SDS-n; the amount of SDS used was 288.38×8.4×n×V / 1000, n=90; 3) Assembly of aqueous ion batteries The NTP working electrode was used as the negative electrode, the LMO working electrode was used as the positive electrode, the LN-SDS-n was used as the electrolyte, and a separator was added between the positive and negative electrodes to assemble the R2032 button cell. The mass of NTP on the negative electrode was 2-3 mg cm -2 , the ratio of the mass of LMO on the positive electrode to the mass of NTP on the negative electrode is 13:
12.
3. The assembly method according to claim 2, characterized in that: The electrode material powder described in step 1) includes NTP powder and LMO powder; In step 1), the mass ratio of electrode material powder, acetylene black and polyvinylidene fluoride is 8:1:1; In step 1), the current collector is a stainless steel wire mesh or a carbon cloth.
4. The assembly method according to claim 2, characterized in that: Step 3) The diaphragm is Whatman TM GF / A glass fiber paper or BH5510 sulfonated diaphragm.
Citation Information
Patent Citations
Novel water system secondary battery taking lithium salt and sodium salt as electrode materials
CN107180966A
Aqueous zinc ion battery electrolyte and application thereof
CN111900497A
Lithium ion battery with wide working temperature range
CN111952670A